Faktor-Faktor yang Berhubungan dengan Kejadian Kecelakaan Lalu Lintas pada Pengendara Sepeda Motor di Daerah Mimika, Papua, Tahun 2022 - Indasari, Riska; Ayu, Ira Marti; Situngkir, Decy; Nitami, Mayumi (Jurnal Kesmas Jambi, 2024)
The most traffic accidents in the Mimika Resort Papua Region in 2020-2022 were for motorbike users compared to cars. Accident data from the Mimika Resort Papua Regional Traffic Unit found 124 traffic accidents in 2020, 137 incidents in 2021, and 169 incidents in 2022. This research aims to determine the factors related to traffic accidents among motorbike drivers in Papua Mimika Resort in 2022. This research was conducted in December 2022-August 2023. This research used an analytical cross-sectional design with a sample size of 152 motorbike drivers. Sampling used simple random sampling. The independent variables are driver condition, health problems, vehicle condition, road conditions, and environmental conditions, and the dependent variable is traffic accidents. Data will be analyzed using univariate and bivariate analysis using the chi-square test. Univariate results showed that the highest proportion was seriously injured victims (42.1%), driver conditions were at risk (86.8%), health problems were at risk (50.7%), vehicle conditions were not at risk (83.6%), road conditions not at risk (57.9%) and environmental conditions are not at risk (87.5%). Bivariate results show that there is a relationship between health problems and the incidence of traffic accidents (PR= 2.59; 95%CI: 1.29-5.21), while the variable that is not related is the condition of the driver (PR= 1.51; 95 %CI: 0.51-4.50), vehicle condition (PR= 1.36;95%CI: 0.66-2.79), road condition (PR= 1.46;95%CI: 0.80 -2.66), and environmental conditions (PR= 0.96; 95%CI: 0.38-2.44). The police should always provide education to the public about the dangers of driving while under the influence of excessive alcohol in traffic accidents.